Management of cases testing positive for gonococcal infection in a community-based chlamydia screening programme. Issue 6 (12th October 2010) - Downing, Jennifer; Cook, Penny A; Madden, Hannah C E; Phillips-Howard, Penelope A; Higgins, Stephen P; Bellis, Mark A
Abstract : Background: The National Chlamydia Screening Programme in Greater Manchester (NCSP-GM) commissioned an evaluation of the management of gonorrhoea cases identified using the Gen-Probe APTIMA Combo 2 assay (AC2). Methods: NCSP-GM provided data on gonorrhoea cases from a 6-month period (September 2007–February 2008). Data were collected from patient referral pathways to genitourinary medicine (GUM) clinics, including confirmatory testing, antibiotic resistance patterns and contact tracing. The AC2 positive predictive value (PPV) was calculated. Results: 111 individuals tested positive for gonococcal infection using AC2 (0.7% of 16 028 individuals tested). Of these, 96 (0.6% of all tested) known index cases were seen at Greater Manchester GUM clinics. 78/96 (14 men, 64 women) underwent confirmatory microscopy and gonococcal culture. Confirmatory tests were positive in 14 men (100%) but only 40 women (63%). Thus the PPV of AC2 was 69% (54/78). Sensitivity in women may have been reduced by limited partner information and sample-taking (only 28% had a full gonorrhoea screen). Conclusion: Gonorrhoea screening in an NCSP-targeted population identified gonorrhoea in a low-risk population. Subsequent management in GUM clinics was variable and limited sample-taking may have decreased the sensitivity of confirmatory testing in women. Appropriate antibiotic sensitivity tests or, in their absence, a test of cure may be needed to ensure effective treatment.